Impact of a training programme on food preparation knowledge and skills of food service workers at Sharpeville care of the aged - Sinthumule, Lufune (My University, 2010)
Introduction: The education, training and development (ETD) industry has developed fast over the past few years in our country. One need only read the national weekend papers and see all the ETD vacancies advertised to realise that ETD issues are being given increased coverage in this country. The reason for this increased focus on ETD is the need for skilled workers in organisations. Reports on our competitiveness in the world have consistently identified the lack of people development as a major stumbling block for the South African economy in competing in the global market. Objectives: The main objective of this study was to measure the impact of a training programme for the food service workers providing meals to 300 elderly people attending the Sharpeville Care of the Aged centre, in terms of a skills development programme, in order to contribute to increased productivity and provide nutritious meals to the elderly. Methods: A baseline survey was undertaken to determine the nutritional status, food consumption patterns and nutrient intake in a random sample of 300 elderly people attending the care centre five days a week. Socio-demographic and health questionnaires, as well as 24-hour recall questionnaires were completed with the assistance of trained fieldworkers. Anthropometric measurements included weight, height, and Mid-Upper Arm Circumference. Furthermore, the existing menus served to the elderly were theoretically analysed using FoodFinder® version 3 program to determine the energy, carbohydrate, protein and fat content. A developed and tested questionnaire was used to gather information from ten volunteer food service workers at the care centre to determine the training needs. The results of the baseline survey, the menu analysis and training needs assessment were used to develop a training programme that was implemented for a period of ten weeks. Learning was measured after the training programme by administering the same knowledge questionnaire, as well as by a portfolio of evidence and practical assessment. Data analyses: Data for the baseline survey was captured on an Excel spreadsheet. Data analysis was done using the Statistical package for Social Sciences (SPSS) for Windows version 10.0 program for all variables except dietary intake data. Dietary intake and food consumption data were analysed by a registered dietician using the FoodFinder® version 3 program, developed by the Medical Research Council (MRC). Daily nutrient intakes were reported as means and standard deviations and compared to RDAs. Paired t tests were done to determine correlations between knowledge of the food service workers before and after the implementation of the training programme. Results: The results indicated that the majority of the elderly had an income of between R500 and R1 000 per month and most of them reported an occasional lack of funds to meet basic household needs, confirming the presence of food insecurity. Daily dietary intakes (mean ±Standard Deviation [SD] were 5 041,2 ± 2 299,6 kilojoules (kJ) energy, 50,4 ± 28,2 gram (g) protein, 38,9 ± 28,2 g fat and 149,0 ± 76,6 g carbohydrates. The majority (29.5%) were overweight (body mass index [BMI] ~25) or obese (BMI ~30) whilst 33.5% had a mid-upper arm circumference (MUAC) of ~21.7 centimetres (em). Mean intakes of micronutrients were low in comparison with the reference standards. The volunteer food service workers were literate as the majority had higher than grade 10-12 training and 80% had previously received on-the-job training. The training programme was successfully implemented and the knowledge of the voluntary food service workers improved after the training programme was implemented. However, because of the small sample size no significance could be determined. Conclusions: The findings of this study confirmed that poverty, malnutrition, both under- and over-nutrition, as well as household food insecurity and poor health were the major problems observed in this elderly community. These findings correspond to other studies, however limited, conducted amongst the elderly in South Africa. The results indicated that, although the food service workers were literate and had received prior training, they still had a poor knowledge of appropriate food preparation method and practices, as well as nutrition, especially related to the elderly. On completion of the training programme, the knowledge of the food service workers improved. This study emphasises the importance of continued on-the-job training Recommendations: The recommendations of further research include: 1) A more detailed study to evaluate the influence of the training programme not only on knowledge and skills, but also on behaviour and attitude. 2) Periodically measuring such influence over a year to measure knowledge retention. 3) Implementation of a NEP for the elderly and its impact on nutrition knowledge and dietary intake behaviour tested.
M. Tech. (Department of Hospitality, Faculty of Human Sciences) Vaal University of Technology
Keywords: Education training and development; Skilled workers; Food service workers; Meals for the elderly; FoodFinder® version 3; Nutrition for the elderly; 613.20846; Aged -- Nutrition.; Aging -- Nutritional aspects.